53 undergraduates improve their English language skills - UMP, PNC
A total of 53 undergraduates Universiti Malaysia Pahang (UMP) spent their semester break by taking part in the Wonderful World of English Camp as part of their efforts to build up self-confidence so they could communicate better in the language.